Peningkatan Keterampilan Praktik Sains Siswa Melalui Model Pembelajaran Experiential Learning pada Siswa Kelas V MI Muhajirin Kota Jambi - Niken Legowo (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
Adapting to the demands of the independent learning curriculum is important for students to have practical science skills. This research aims to improve the practical science skills of class V MI Muhajirin Jambi City students through the application of the Experiential Learning learning model. This model was chosen because it can provide students with direct experience in understanding science concepts, thus encouraging active involvement and mastery of practical skills. The research method used is classroom action research (PTK) with a two-cycle design, where each cycle consists of planning, implementation, observation and reflection. Data was collected through observation, practical skills assessment sheets, and interviews with students.